Small airways dysfunction in patients with systemic sclerosis and interstitial lung disease - Panagopoulos, Panagiotis K.; Goules, Andreas V.; Georgakopoulou, Vasiliki E.; Kallianos, Anastasios; Chatzinikita, Eirini; Pezoulas, Vasileios C.; Malagari, Katerina; Fotiadis, Dimitrios I.; Vlachoyiannopoulos, Panayiotis; Vassilakopoulos, Theodoros; Tzioufas, Athanasios G. (Frontiers in Medicine, 2022)
Background A number of studies report small airways involvement in patients with systemic sclerosis (SSc). Furthermore, small airways dysfunction is increasingly recognized in patients with interstitial lung disease (ILD) of idiopathic or autoimmune etiology. The objectives of this study were to evaluate small airways function in SSc patients with ILD and explore the effect of treatment on small airways function by using conventional and contemporary pulmonary function tests (PFTs). Methods This single-center, prospective, observational study included a total of 35 SSc patients, with and without ILD based on HRCT scan, evaluated by a special radiologist blindly. Clinical data were collected from all patients who were also assessed for HRCT findings of small airways disease. Small airways function was assessed by classic spirometry, measurement of diffusing capacity for carbon monoxide, body plethysmography, single breath nitrogen washout (N2SBW) and impulse oscillometry (IOS). The prevalence of small airways dysfunction according to R5–R20, phase III slopeN2SBW and CV/VC methodologies was calculated in the total SSc population. Pulmonary function tests were compared between: (a) SSc-ILD and non-ILD patients and (b) two time points (baseline and follow up visit) in a subset of SSc-ILD patients who received treatment for ILD and were re-evaluated at a follow up visit after 12 months. Results Phase III slopeN2SBW and R5–R20 showed the highest diagnostic performance for detecting small airways dysfunction among SSc patients (61 and 37.5%, respectively). Twenty three SSc patients were found with ILD and 14 of them had a 12-month follow up visit. SSc-ILD patients compared to those without ILD exhibited increased phase III slopeN2SBW ≥120% (p = 0.04), R5–R20 ≥0.07 kPa/L/s (p = 0.025), airway resistance (Raw) (p = 0.011), and special airway resistance (sRaw) (p = 0.02), and decreased specific airway conductance (sGaw) (p = 0.022), suggesting impaired small airways function in the SSc-ILD group. Radiographic features of SAD on HRCT were observed in 22% of SSc-ILD patients and in none of SSc-non-ILD patients. Comparison of PFTs between baseline and follow-up visit after 12 months in the 14 SSc-ILD treated patients, showed improvement of phase III slopeN2SBW (p = 0.034), R5–R20 (p = 0.035) and Raw (p = 0.044) but not sRaw and sGaw parameters. Conclusion Phase III slopeN2SBW and R5–R20 may reveal small airways dysfunction in SSc associated ILD before structural damage and may be partially improved in a subset of patients receiving treatment for ILD.